Peranan Kepolisian dalam Menindak Pelaku Pemerkosaan terhadap Anak Kandung - Maharani Maharani; Enny Ristanti; Nahdiya Shabrina (Bhirawa Law Journal, 2021)
The crime of rape is the case that causes the most difficulties in its resolution, both at the stage of investigation, prosecution, and at the stage of making a decision. In this study, the formulation of the problem is "What is the role of the police in taking action against the perpetrators of the crime of rape against biological children in the Malang City Police area?" and "How is the legal protection for victims of the crime of rape against biological children in the Malang City Police area?". The research method used by the author is Juridical Empirical. Based on the results of this study, the police in taking action against the perpetrators of the crime of raping their biological children must wait for a report from the victim or the aggrieved party then the police will take action to arrest and then investigate and investigate at PPA Polres Malang City. Legal protection for victims of rape at the Malang City Police is by not publishing the case. The crime of rape in the Criminal Code is regulated as a crime of decency that includes rehabilitation efforts from institutions and outside the institution, providing safety guarantees for victim witnesses and expert witnesses both physically and mentally.